(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2019)
The suggestions for the engineering calculation of the reinforced concrete flexural members strength during the elastic work of steel are given. The engineering technique is developed on the basis of a nonlinear deformation model application using fractionally rational function for describing the process of concrete compressed area deformation and other prerequisites that are recommended by current norms for the reinforced concrete structures design. The analytical dependences have been obtained for determining the neutral axis depth and the calculation of the internal bending moment value perceived by the beam in the normal section. The task of determining the load-bearing capacity of the bending element is reduced to searching by the direct analytical dependences the maximum value of the bending moment that can be perceived by the beam at given strains of the most compressed rib of a cross-section.